2002
DOI: 10.1183/09031936.02.00266302
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in children exposed to nitrogen dioxide in ice arenas

Abstract: Very high concentrations of nitrogen dioxide (NO 2 ) have been measured in arenas using combustion engine-powered resurfacing machines. This study was performed to compare the occurrence of asthma in children playing ice hockey in arenas using propane-powered machines and in children attending arenas using electric machines.Children regularly playing hockey in the arenas (nine propane, six electric) were sent a questionnaire, including questions on allergic disease and risk factors. Measurements of NO 2 were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Recent work has found a higher incidence rate of EIB among Olympic winter athletes than that of the typical athletic population . A similar incidence rate has also been found among hockey players and figure skaters (Rundell 2004a;Rundell et al 2004b;Game et al 2003;Thunqvist et al 2002;Leuppi et al 1998;Mannix et al 1996;ProvostCraig et al 1996). Specifically, it has been suggested that air pollutants emitted by fuel-powered ice resurfacing machines and possible indoor mould concentrations may contribute to the high incidence rate of EIB in skating athletes (Game et al 2003;Rundell 2004a;Rundell et al 2004b;ProvostCraig et al 1996;Wilber et al 2000).…”
Section: Introductionsupporting
confidence: 69%
“…Recent work has found a higher incidence rate of EIB among Olympic winter athletes than that of the typical athletic population . A similar incidence rate has also been found among hockey players and figure skaters (Rundell 2004a;Rundell et al 2004b;Game et al 2003;Thunqvist et al 2002;Leuppi et al 1998;Mannix et al 1996;ProvostCraig et al 1996). Specifically, it has been suggested that air pollutants emitted by fuel-powered ice resurfacing machines and possible indoor mould concentrations may contribute to the high incidence rate of EIB in skating athletes (Game et al 2003;Rundell 2004a;Rundell et al 2004b;ProvostCraig et al 1996;Wilber et al 2000).…”
Section: Introductionsupporting
confidence: 69%
“…Moreover, hockey players are in contact with carbon monoxide, nitrogen monoxide and nitrogen dioxide contained in the air of sports facilities (produced by ice cleaning machines). A study conducted by Thunqvist et al (2002) showed that children playing hockey in facilities with an increased N2O content (mean concentration 510 ug/m3) more often suffered from symptoms of rhinitis and wheezing respiration in comparison with children playing in facilities where the concentration of this gas was low (mean 89 ug/m3).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of NO 2 are fluctuating and are higher outdoors during wintertime, reaching the highest levels at rush-hour (13). Indoors the levels can be even higher than outdoors when unvented gas fuelled stoves are used and also in skating ice rinks (14,15).…”
Section: No 2 and Its Chemical Propertiesmentioning
confidence: 99%